Criminal Sanctions as a Last Resort in Environmental Law Enforcement: A Study of Mining Pollution in Palu and Donggala - Lestari, Titie Yustisia; Sari, Dewi Kemala; Hasnawati, Hasnawati (Universitas Internasional Batam, 2025)
Environmental pollution from mining activities in Indonesia, particularly in Palu City and Donggala Regency, presents complex legal challenges as the country strives to enforce environmental protection laws effectively. The core legal issue addressed in this research is the insufficient implementation of criminal sanctions despite the evident environmental degradation caused by licensed mining operations, which often only receive administrative sanctions without achieving deterrence or restoration. This study aims to examine the enforcement of criminal sanctions as a legal mechanism to strengthen environmental law in Indonesia. Utilizing an empirical legal research method through field observations and direct interviews, the research captures the realities of environmental law enforcement in Palu City and Donggala Regency. The findings reveal that although Indonesia's environmental laws provide clear provisions for imposing criminal sanctions on polluters, the practical application remains limited due to administrative hurdles, lack of coordination between central and local governments, and the prioritization of economic interests over environmental protection. However, imposing criminal sanctions is imperative to ensure corporate accountability, prevent further ecological damage, and encourage compliance with environmental quality standards. This study highlights the urgency of positioning criminal sanctions not merely as ultimum remedium but as an integral part of a proactive enforcement strategy, thereby fostering sustainable development while safeguarding environmental integrity. The insights from this research are intended to guide policymakers, law enforcers, and environmental advocates in improving the effectiveness of environmental criminal law enforcement in Indonesia, ensuring a balanced approach between economic growth and environmental sustainability.